Efficient Cleavage of Lignin–Carbohydrate Complexes and Ultrafast Extraction of Lignin Oligomers from Wood Biomass by Microwave‐Assisted Treatment with Deep Eutectic Solvent. Issue 8 (1st March 2017) - Liu, Yongzhuang; Chen, Wenshuai; Xia, Qinqin; Guo, Bingtuo; Wang, Qingwen; Liu, Shouxin; Liu, Yixing; Li, Jian; Yu, Haipeng
Abstract: Lignocellulosic biomass is an abundant and renewable resource for the production of biobased value‐added fuels, chemicals, and materials, but its effective exploitation by an energy‐efficient and environmentally friendly strategy remains a challenge. Herein, a facile approach for efficiently cleaving lignin–carbohydrate complexes and ultrafast fractionation of components from wood by microwave‐assisted treatment with deep eutectic solvent is reported. The solvent was composed of sustainable choline chloride and oxalic acid dihydrate, and showed a hydrogen‐bond acidity of 1.31. Efficient fractionation of lignocellulose with the solvent was realized by heating at 80 °C under 800 W microwave irradiation for 3 min. The extracted lignin showed a low molecular weight of 913, a low polydispersity of 1.25, and consisted of lignin oligomers with high purity (ca. 96 %), and thus shows potential in downstream production of aromatic chemicals. The other dissolved matter mainly comprised glucose, xylose, and hydroxymethylfurfural. The undissolved material was cellulose with crystal I structure and a crystallinity of approximately 75 %, which can be used for fabricating nanocellulose. Therefore, this work promotes an ultrafast lignin‐first biorefinery approach while simultaneously keeping the undissolved cellulose available for further utilization. This work is expected to contribute to improving the economics of overall biorefining of lignocellulosic biomass. Abstract : Faster with microwaves : A choline chloride/oxalic acid dihydrate deep eutectic solvent (DES) is used for fractionation of wood lignocellulose (WL). A combination of DES and microwave irradiation has a synergetic effect on efficiently cleaving lignin–carbohydrate complexes and ultrafast fractionation of WL. The extracted lignin fraction is of low molecular weight, low polydispersity, and high purity.